Life cycle environmental impacts of utilizing hemp seed meal as a protein source in sheep feedlot rations - Clark, Samantha Maye, author; Dillon, Jasmine, advisor; Archibeque, Shawn, committee member; Nachappa, Punya, committee member; DiVerdi, Joseph, committee member (Colorado State University. Libraries, 2023)
Hemp seed meal is a protein-rich byproduct of the hemp industry, obtained from the cold press extraction process used to produce hemp oil. The objective of this work was to evaluate the environmental impact of using hemp seed meal as a protein supplement in sheep production. A cradle-to-gate life cycle assessment (LCA) was conducted on three sheep production systems which differed in the feedlot phase: one fed a feedlot ration containing soybean meal as the protein source (soybean meal diet), one fed hemp seed meal in the feedlot ration (hemp diet), and one fed organic hemp seed meal in the feedlot ration (organic hemp diet). Animal performance data were collected from a nutrition trial. Hemp production, harvest, and processing data were provided by a hemp product company. Economic and physical allocation were applied to the hemp diet systems, and the ReCiPe Midpoint (H) methodology was used to calculate the global warming (i.e., carbon footprint), water consumption, land use, and fossil resource scarcity impacts on a per kg lamb live weight basis for each system. Carbon footprint ranged from 10.1 to 11.4 kg CO2eq/kg LW, water consumption ranged from 1.3 to 4.2 m3/kg LW, fossil resource scarcity ranged from 0.5 to 0.8 kg oil eq/kg LW, and land use ranged from 2.8 to 6 m2a crop eq/kg LW. Impact assessment results were not sensitive to a 10 or 20% increase in electricity demand at processing. The use of IPCC Tier 2 methods for estimating enteric methane emissions from sheep resulted in a 7.5–8.5% increase in the carbon footprint, relative to a mechanistic equation present in the Ruminant Nutrition System model. Physical allocation resulted in greater impacts of the hemp diet systems than the soybean diet systems for all categories except land use. However, economic allocation resulted in greater impacts for the soybean diet systems than the hemp diet systems for all categories evaluated. This was explained by inherent differences between the allocation method, as physical allocation attributed 80% of the environmental burden to hemp seed meal, while economic allocation attributed 0% of the environmental burden to hemp seed meal due to the current lack of an economic value for hemp seed meal. The production volume of dependent products ("dependent products", or products for which a change in demand does not affect production volume, commonly referred to as co- or byproducts) are driven by monetary value of the determining product (the product for which a change in demand affects the production volume), but relationships between co-products change overtime. Therefore, as the hemp industry continues to develop, an economic value may be placed on hemp seed meal with implications for its relative ability to reduce the environmental impacts of livestock production. As agricultural industries strive to become more environmentally efficient, they must be adaptive to changes in both monetary value and environmental impact, which are intrinsically related. This research demonstrated the importance of allocation choice in assessing the impact of feeding byproducts on the environmental impact of livestock production systems. Economic allocation better reflected the monetary driving factor for hemp production than physical allocation. As such, the inclusion of hemp seed meal in a feedlot ration reduced the environmental impact of sheep production systems.